Urticaria: Its History-Based Diagnosis and Etiologically Oriented Treatment - Maurer, Marcus (Deutscher Arzte Verlag, 2008)
INTRODUCTION: The term „urticaria“ refers to any of a group of distinct skin conditions that are characterized by itchy, wheal-and-flare skin reactions (hives). In spontaneous urticaria, the most common type, the hives seem to arise without provocation. METHODS: Selective review of the literature, including current guidelines. RESULTS: Spontaneous urticaria is divided into acute (lasting less than six weeks) and chronic types. The pathognomonic itching, hives, and angioedema arise by the same mechanism – cutaneous mast cell activation and release of histamin and other mediators of inflammation – in both acute and chronic urticaria, but these two disorders have different etiological profiles. The underlying cause of acute urticaria cannot be identified in about half of all cases. Chronic urticaria, which is much rarer, is usually caused by autoreactivity, chronic infection, or intolerance to food additives. If the condition persists after the underlying cause has been treated or eliminated, non-sedating antihistamines are the agents of first choice for symptomatic treatment. DISCUSSION: Unlike acute urticaria, which is self-limited and should be treated symptomatically, chronic urticaria should be treated by the identification and elimination of underlying causes, which is usually curative.